Analisis pendekatan-pendekatan dalam pengembangan kurikulum PAI - Puteri, Aulia Rahmah; Asmiralda, Febrina; Miftahuljannah, Viona; Halimah, Siti (Innovative: Journal Of Social Science Research, 2025)
This study discusses various approaches used in the development of the Islamic Religious Education (PAI) curriculum. The purpose of the research is to identify the characteristics and advantages of each approach within the PAI curriculum. The method used is a literature review with descriptive analysis. The results show five main approaches: the academic subject approach, humanistic approach, technological approach, social reconstruction approach, and competency-based approach. Each approach has strengths that can help improve students’ understanding and character development. This study concludes that selecting and combining the right approaches is crucial for the PAI curriculum to be effective and relevant to the needs of the times.